2018
DOI: 10.1111/bph.14487
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of bee venom and its major component, melittin, on atopic dermatitis in vivo and in vitro

Abstract: Background and PurposeAtopic dermatitis (AD) is a multifactorial skin condition with complex interactions of innate and adaptive immune responses. There are several existing therapies for AD, including topical glucocorticosteroids, emollients, phototherapies, calcineurin inhibitors and immunosuppressants, such as cyclosporine A. Although these therapies reduce inflammation, they also cause serious side effects. Therefore, it is necessary to develop new therapeutic approaches for AD treatment without side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 64 publications
5
53
0
Order By: Relevance
“…Given the anti-inflammatory properties of bee venom, various forms of traditional bee venom treatment, including stings, venom injections, and venom acupuncture, have been used to alleviate pain and to treat chronic inflammatory diseases, such as rheumatoid arthritis and multiple sclerosis [2,4,5]. In addition, our previous studies suggested that bee venom attenuates atherosclerosis atopic dermatitis and periodontitis by the suppression of pro-inflammatory cytokines [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Given the anti-inflammatory properties of bee venom, various forms of traditional bee venom treatment, including stings, venom injections, and venom acupuncture, have been used to alleviate pain and to treat chronic inflammatory diseases, such as rheumatoid arthritis and multiple sclerosis [2,4,5]. In addition, our previous studies suggested that bee venom attenuates atherosclerosis atopic dermatitis and periodontitis by the suppression of pro-inflammatory cytokines [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, honeybee venom contains many low molecular mass compounds such as sugars, amino acids, phospholipids, pheromones and biogenic amines [2]. Extensive research conducted in recent years has shown that satisfactory results may be achieved when using bee venom for various types of diseases such as arthritis [3], chronic pain [4], cancer [5] and atopic dermatitis [6]. The major component of bee venom is called melittin.…”
Section: Introductionmentioning
confidence: 99%
“…BV treatment has been used to treat various inflammatory diseases. There are several recent studies about the biological and pharmacological activities of BV, proposing that BV inhibits the increase of inflammatory and pro-inflammatory cytokines from the human keratinocytes [6][7][8]. This study investigated whether BV treatment had anti-inflammatory effects on AD using LPSactivated murine keratinocytes and PA-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…BV is composed of many peptides, including melittin, apamin, adolapin and mast cell degranulating peptide. Among them, melittin is the key component which accounts for 50% of dry weight of BV and it has been investigated to determine its biological and pharmacological activities [6]. A recent review of treatment with BV reported antiinflammatory, anti-apoptotic, antibacterial, and anticancer effects [7].…”
Section: Introductionmentioning
confidence: 99%